A system analysis of LKAB Malmberget heating system to centralisation and substitution of fossil fuels to biofuels - Riesbeck, Johan; Sandberg, Johan; Wang, Chuan (Swerea MEFOS AB, 2012)
An industrial heating system connected to an iron ore mine and iron ore upgrading processing system is presented. The profitability of introducing measures for increased energy efficiency and improved waste heat utilisation has been investigated. The results show that a full centralisation of the system with increased heat recovery and densified wood based boilers is the most financial solution of a life span over twenty years. The system will be more flexible and easy to connect with external users if a centralisation is made. To minimise the risk of increased energy prices it is recommended to increase waste heat utilisation which will be most profitable if the system is centralised. Use of bio based boilers will make the system free from fossil fuels. Upprättat; 2012; 20130506 (ysko)